(untitled) (Journal of Oriental Studies, 2025)
This article presents a comparative analysis of the commentaries (shurūḥ) on al-Hidāya by Burhān al-Dīn al-Marghīnānī (d. 593 AH), produced in Central Asia and the Middle East during the 13th–15th centuries. The purpose of the study is to identify the methodological differences employed by scholars of these two regions while composing their commentaries, and to highlight the significance of these works for the development of Hanafi jurisprudence. The novelty of the research lies in its comprehensive examination of linguistic style, methodological approaches, and the use of sources, with particular attention to the interaction between Central Asian and Middle Eastern scholars in explaining disputed legal issues. Special emphasis is given to the identification of the main sources that influenced the commentators and to the chronological analysis of the transmission chains (isnāds) associated with al-Hidāya. The study also considers differences in the treatment of arguments from other madhhabs, as well as the distinctive role of Central Asian jurists in shaping the Hanafi school in the Middle East. Methodologically, the research applies comparative and textual analysis in order to reveal the similarities and divergences in methodology and style. The findings demonstrate the intellectual interconnectedness between Central Asia and the Middle East, while underlining the richness and diversity of the Hanafi legal tradition. The article will be of interest to historians, orientalists, Islamic scholars, and a broad audience engaged in the study of Islamic civilization in Central Asia. Keywords: al-Hidāya, Hanafi jurisprudence, commentaries, methodology, Central Asia, Middle East, al-Sighnāqī, al-Kurlānī.